A novel frameshift variant of LMX1A that leads to autosomal dominant non-syndromic sensorineural hearing loss: functional characterization of the C-terminal domain in LMX1A. Issue 8 (15th December 2022) - Xiao, Min; Zheng, Yan; Huang, Kuo-Hsiang; Yu, Shanhe; Zhang, Wenbi; Xi, Yanping; Dou, Yan; Sun, Xiaoxi; Lei, Caixia; Yu, Huiqian
Abstract: Non-syndromic sensorineural hearing loss (NSHL) is a group of genetically heterogeneous conditions with broad phenotypic heterogeneity. There is, at present, no curative treatment for genetic hearing loss (HL). Early molecular diagnosis of progressive disorders and elucidation of the causes and pathomechanisms are essential for developing therapeutic strategies. Here, we identified a novel rare frameshift variant of LMX1A (c.915dup), which resulted in the C-terminal-altered and -truncated LMX1A (p.Val306Cysfs * 32). This C-terminal frameshift mutation co-segregated with autosomal dominant (AD) NSHL in a four-generation Chinese family, suggesting that the LMX1A non-missense mutation is also contributed to ADNSHL. In this family, the affected individuals exhibited the variable auditory phenotypes ranging from profound congenital deafness at birth or to mild/moderate HL in adulthood. We also found that the embryonic cells carrying with the heterozygous variant significantly expressed several upregulated HL-associated genes at transcriptional level. In vitro splicing assay suggested that the LMX1A mRNA with c.915dup did not cause nonsense-mediated decay and was translated into a truncated LMX1A. In addition, electrophoresis mobility shift assay and luciferase assays have shown that the highly conserved C-terminal domain (amino acid 306–382) of the LMX1A was required for regulating the protein–DNA interaction and transactivation in vitro . Furthermore, apoptosis assays suggested that the C-terminal domain of the LMX1A was important for mediating apoptosis in the cochlear hair cells. Our work provided the multiline of the evidence to support that non-missense mutation of LMX1A leads to ADNSHL and the C-terminal domain of LMX1A is important for mediating transcriptional activity and associated with promoting apoptosis in the cells.